Scheduling: Algorithms and Applications - Werner, Frank (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint of a Special Issue in the journal Algorithms is dedicated to scheduling algorithms and their various applications. In addition to the Editorial, it contains 12 papers including a survey of assembly and production line design and scheduling under uncertainty. Other topics addressed in this reprint are the energy management of power systems, cost scheduling for financial data supply chains, staff scheduling in the construction industry, various assignment problems, single-lane roundabouts, robotic arm-based batching systems with conveyor belts, as well as single-machine and flow-shop scheduling problems.